Article RETRACTED due to manipulation by the authors Strategies to increase physical activity in elementary school children in the digital age to support a healthy lifestyle - Atikah Rahayu; Hendra Setyawan; Sabariah Sabariah; Rufi’i Rufi’i; Nofri Hendri; Safrudin Safrudin; Nurkadri Nurkadri; Satria Yudi Gontara; Wilasari Arien; Susanto Susanto; Swamynathan Sanjaykumar (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study used the systematic literature review to review strategies to increase physical activity in elementary school children in the digital era to support a healthy lifestyle. Data were obtained from articles searched through Google Scholar. The search was conducted in September 2024 using the keywords: "Physical Activity Promotion" AND "Elementary School" AND "Healthy Lifestyle". During the search, inclusion and exclusion criteria were applied. For example, the search focused on articles published in Scopus-indexed journals between 2019 and 2024. From this initial search, 551 articles were found. Furthermore, they were screened again in several stages, and 16 articles that fit the theme and met the inclusion requirements were yielded. During the article selection, this study followed the PRISMA guidelines. The findings of this study confirmed the importance of appropriate strategies to increase the physical activity of elementary school students in the digital era to support a healthy lifestyle. The use of technology in the form of fitness apps, exergames, and wearable devices was proven effective in motivating children to be physically active. These technologies not only serve as support tools but also as powerful motivators that offer tracking and feedback that can encourage children to engage in physical activity more actively. In addition, more interactive approaches in schools, such as the Sport Education Model (SEM) and Teaching Personal and Social Responsibility (TPSR), have shown significant increases in student participation, resulting in a sustainable impact on daily physical activity habits. This study also reported that family support was very important in increasing children's physical activity. By engaging the whole family in physical activities, whether through shared outdoor activities or fitness apps, an environment that supports a healthy lifestyle is created. In addition, training teachers to utilize technology in physical learning can strengthen the implementation of strategies in schools, creating a more supportive and enjoyable environment for students.